1974
DOI: 10.1080/03015521.1974.10427693
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal distribution of pasture production in New Zealand

Abstract: Pasture growth rates are presented for two sites, Mona Bush and Winton, on the Southland Plains. Yields were obtained from grazing trials cut by a standardised method at regular intervals using a movable cage technique. The mean yield and standard error of individual samples over all years of measurement are given for standard dates at 14-dav intervals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(23 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…At Moginie, the pasture net herbage accumulation (NHA) rate was measured monthly (July and August were combined) using the trim technique (Radcliffe 1974) from April 2005 to March 2006. Three pasture grazing exclusion cages (1.14 9 0.64 m) were placed in the top, middle and bottom of each plot after mowing the pasture to 2.5 cm height.…”
Section: Pasture Dry Matter Samplingmentioning
confidence: 99%
“…At Moginie, the pasture net herbage accumulation (NHA) rate was measured monthly (July and August were combined) using the trim technique (Radcliffe 1974) from April 2005 to March 2006. Three pasture grazing exclusion cages (1.14 9 0.64 m) were placed in the top, middle and bottom of each plot after mowing the pasture to 2.5 cm height.…”
Section: Pasture Dry Matter Samplingmentioning
confidence: 99%
“…At each site, monthly pasture dry matter (DM) accumulation was estimated using the trim technique (Radcliffe 1974). Pasture in caged miniplots (1.14 · 0.64 m) was clipped to simulate grazing every month.…”
Section: Pasture Measurementsmentioning
confidence: 99%
“…Studies by Dennis & Woledge (1987) indicated that reduced stolon branching and subsequent restriction in clover leaf development in spring, as a result of shading by grasses, was a major factor determining reduced clover growth from N fertiliser use. In Waikato, the increase in rate of grass growth in spring is more gradual than that in Southland (e.g., compare Baars (1976) & Radcliffe (1974), and this may reduce the potential for inhibiting effects of N on stolon branching and clover growth.…”
mentioning
confidence: 99%